Art, Power, and Social Change - Rowe, David Emmanuel (Social justice, 2006)
A special issue on art, power, and social change is presented. Articles discuss counter-revolution, the spectacle, and the situationist avant-garde; formalist art criticism and the politics of meaning; the excellence-access debate in U.S. arts policy; the politics of culture and the art of dissent in early modern Japan; political culture in Hong Kong and Taiwan; the mobilization of youth for social change in the post-civil rights era; art for social change rom the Homelessness Photography Project; photography as art of the mssing; Mexican art, social movements, and Anzaldúa's “Conocimiento”; and new transdisciplinary visualities as an alternative to redistribute the power of thought.